Investor Psychology Towards Gold: Is It Still Attractive in a Green Portfolio? - Anjum Gupta; Dr. Parul Bhatia (Goodwood Publishing, 2026)
Purpose: This study examines changes in investor psychology in the field of gold investments, investigating whether traditional motives, such as emotional attachment, remain dominant or whether new rationales emerge in a volatile global environment. Research Methodology: A structured questionnaire survey was conducted with more than 130 respondents in the study. The analysis employed descriptive statistics (mean and standard deviation), Exploratory Factor Analysis (EFA), and inferential tests to analyze the effects of liquidity, portability, sustainability, policy support, and perceived green potential on the gold investment preferences. Results: The findings reveal that liquidity and policy support are the most influential determinants of gold investment decisions. Emotional motivations, historically central to gold possession in India, have diminished in importance. Global and national events, including COVID-19, the Ukraine conflict, U.S. elections, Indian government transitions, and China’s economic shifts, have reinforced gold’s role as a financially sustainable and safe-haven asset. Investor psychological preferences, however, remain heterogeneous. Conclusions: The study concludes that investor behavior is shifting from traditional emotional motives toward rational considerations influenced by liquidity, policy, and global economic events. Gold is increasingly perceived as a sustainable investment rather than merely a cultural or emotional asset. Limitations: The sample size and the use of self-reported perceptions limit the study, as they may limit generalizability. Contributions: This research enriches behavioral finance literature by identifying evolving motives in gold investment and provides policy implications for promoting the green potential of gold through taxation incentives and financial innovation.